2019
DOI: 10.1021/acsearthspacechem.9b00058
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Isomerization and Infrared Band Strengths of Two Conformational Isomers of Cyclopropanecarboxaldehyde, a Candidate Interstellar Molecule

Abstract: At least a dozen of the known interstellar molecules possess a formyl group (HCO), suggesting that other such species exist and await discovery in the interstellar medium. Here we examine the mid-infrared (mid-IR) spectrum and selected physical properties of one such candidate, cyclopropanecarboxaldehyde, in amorphous ices. Mid-IR transmission spectra of solid cyclopropanecarboxaldehyde are presented for the first time and used to determine the cis-to-trans ratio of conformational isomers present in amorphous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This result can be compared to those previously reported for the relative stability of CPCA isomers, which seem fairly ambiguous. Durig & Little (1988), Durig et al (1992) and Bartell & Guillory (1965) in their respective experiments found that the cis isomer was the most stable species in the gas phase, with an energy difference of around 40-60 cm −1 , while Hudson & Coleman (2019) showed that the cis/trans ratio was 1:1. On the other hand, Volltrauer & Schwendeman (1971) proposed that in the gas phase the trans species was slightly more stable (10±20 cm −1 ) than the cis one, but with large uncertainties.…”
Section: Rotational Spectrum and Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…This result can be compared to those previously reported for the relative stability of CPCA isomers, which seem fairly ambiguous. Durig & Little (1988), Durig et al (1992) and Bartell & Guillory (1965) in their respective experiments found that the cis isomer was the most stable species in the gas phase, with an energy difference of around 40-60 cm −1 , while Hudson & Coleman (2019) showed that the cis/trans ratio was 1:1. On the other hand, Volltrauer & Schwendeman (1971) proposed that in the gas phase the trans species was slightly more stable (10±20 cm −1 ) than the cis one, but with large uncertainties.…”
Section: Rotational Spectrum and Analysismentioning
confidence: 98%
“…In addition, CPCA was investigated by infrared (IR) and Raman spectroscopy (Durig & Little 1988;Durig et al 1992;Durig & Shen 2000;Hudson & Coleman 2019) and electron diffraction (Bartell & Guillory 1965). In these works the abundance ratios for both cis and trans isomers were derived and it was found that the cis isomer is more stable in the gas phase while the trans is the only species present in liquid phase, which is in contrast with the rotational spectroscopy study (Volltrauer & Schwendeman 1971).…”
Section: Introductionmentioning
confidence: 99%
“…solid, liquid or gas, which can favour one conformer with respect to the others. For example, intermolecular interactions that are present in the solid state can preferentially stabilise one conformer with respect to another [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the liquid phase, the stability appears to be reversed and the anti species is the most stable [13]. This only apparent difference is justified by the stronger dipole moment of the anti conformer with respect to syn, which allows the formation of stronger intermolecular interactions in the condensed phase [3,4,13]. The stability of CPCA conformers was also analysed by NMR spectroscopy in a freon matrix at T=103 K and the results clearly point out a larger stability of the anti conformer with respect to syn, with an energy barrier of 21.0 kJ mol −1 [18].…”
Section: Introductionmentioning
confidence: 99%